Live by the sword, die by the sword: Measuring belief in a just world with popular sayings - Linhares, Layanne Vieira (2022)
Popular sayings express some cultural truth and indicate how individuals are integrated with their social environment. We have proposed that some popular sayings express belief in a just world (BJW) and so they can be a good measure of this belief. We conducted five studies in which we developed a new scale based on the idea that endorsing such popular sayings can measure individual differences in expressing BJW. In studies 1 and 2, we developed a scale of the BJW based on popular sayings (BJWPS). We analyzed its factorial validity by showing that these sayings share the same basic idea: the expression of belief in a just world. Study 3a addressed the convergent validity of the BJWPS, since it correlated positively with other BJW scales and went further by showing their incremental validity by predicting secondary victimization. In addition, Study 3b examined the discriminant validity between the BJWPS and individuals’ attitudes regarding an unvictimized target. In Study 4, we experimentally addressed the predictive validity of the BJWPS in the context of victimization. In summary, the results we presented in the studies provide evidence of validity and reliability in using the popular sayings proposed to measure BJW.